2013
DOI: 10.1080/00207144.2013.810485
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Hypnosis on Anxiety, Depression, Fatigue, and Sleepiness in People Undergoing Hemodialysis:A Clinical Report

Abstract: This study investigated the effect of hypnosis on anxiety, depression, fatigue, and sleepiness in hemodialysis patients. Twenty-nine patients participated in the 15-day study. A single hypnosis session was performed on Day 8. Anxiety, depression, fatigue, and sleepiness were measured at baseline, on Day 8, and on Day 15 (HADS, MFI, ESS). Daily fatigue was also measured numerically. Anxiety, depression, and sleepiness significantly decreased after hypnosis. Weekly measures of fatigue remained stable; however, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 20 publications
0
8
0
1
Order By: Relevance
“…Vahedian-Azimi et al 36 reported that a 60-minute massage reduced systemic blood pressure of patients in the ICU, and Nerbass et al 37 found that a chair massage on 3 consecutive nights reduced pain and fatigue in patients who had undergone bypass surgery. Mental imagery has been used to reduce pain, anxiety, and sleepiness in hemodialysis patients, 15 although its use has not been previously reported in the PCU or ICU, to our knowledge. Although only 45 patients used the guided-imagery intervention, those who did found it to be very helpful.…”
Section: Outcome Measuresmentioning
confidence: 94%
See 2 more Smart Citations
“…Vahedian-Azimi et al 36 reported that a 60-minute massage reduced systemic blood pressure of patients in the ICU, and Nerbass et al 37 found that a chair massage on 3 consecutive nights reduced pain and fatigue in patients who had undergone bypass surgery. Mental imagery has been used to reduce pain, anxiety, and sleepiness in hemodialysis patients, 15 although its use has not been previously reported in the PCU or ICU, to our knowledge. Although only 45 patients used the guided-imagery intervention, those who did found it to be very helpful.…”
Section: Outcome Measuresmentioning
confidence: 94%
“…These interventions have demonstrated beneficial effects on pain, [10][11][12] anxiety, [13][14][15] and insomnia. [16][17][18][19][20][21][22][23] Substantial evidence supports the positive effects of clinical massage on various types of pain, including pain from labor, 10 neck and back pain, 11,27 and, in particular, cancer pain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This includes parameters such as respiratory rate, oxygenation, heart rate, blood pressure, hemostasis, burn injury, and pain. [19][20][21][22] In a mass casualty situation, there are many types of injuries with varying degrees of severity. As the providers may not be trained medical hypnotherapists, the best strategy would be a script that serves as a template that includes somewhat general suggestions.…”
Section: Hypnosis In Mass Casualty Situationsmentioning
confidence: 99%
“…Hypnosis is an intervention that has been shown to be effective in treating anxiety related to various medical conditions, including hemodialysis, atypical cardiac disorder, bone marrow biopsies, colonoscopy, postoperative surgery, emergency dental extraction, and large-core breast biopsy (Chan, 2012; Elkins et al, 2006; Gow, 2006; Lang et al, 2006; Massarini, Rovetto, & Tagliaferri, 2005; Snow et al, 2012; Untas et al, 2013). Studies investigating the use of hypnosis in controlling anxiety in cancer patients found that hypnosis interventions significantly decreased anxiety (Genuis, 1995).…”
mentioning
confidence: 99%